The Relationship between Health Literacy and Rehospitalization among Patients with Myocardial Infarction - Navid Mohammadi; Zahra Soroosh; Marzieh Nojomi; Maryam Motamedkhah (Shiraz University of Medical Sciences, 2023)
Background: Cardiovascular disease, the first leading cause of death worldwide, is associated with different consequences, including rehospitalization. Health literacy (HL) is a factor with potential effects on rehospitalization. This study aimed to examine the relationship between HL and rehospitalization among patients with myocardial infarction (MI).Methods: This prospective cohort study was conducted in 2015-2017. Participants were 366 hospitalized patients with MI who were conveniently recruited from four teaching hospitals in Tehran, Iran. A demographic questionnaire and the Health Literacy for Iranian Adults instrument were completed for participants at the time of their hospital discharge. One month after hospital discharge, thirty-day rehospitalization was assessed over telephone. The SPSS program (v. 16.0) was used to analyze the data through the Chi-square test, independent-sample t test, one-way analysis of variance, Pearson's correlation analysis, and logistic regression analysis.Results: T he t otal m ean s core o f H L w as 5 3.08±16.64 ( in the possible range of 0-100). Most participants (78.6%) had inadequate or barely adequate HL. At the time of rehospitalization assessment, fifteen participants were inaccessible. Among the remaining 351 participants, 28 (8%) reported thirty-day rehospitalization. The mean scores of HL among the participants with and without rehospitalization were 55.36±19.06 and 53.08±16.53, respectively. Logistic regression analysis showed that after adjusting the effects of potential confounders, HL had a significant relationship with rehospitalization (odds ratio=1.05; 95% confidence interval: 1.007-1.1; P=0.024).Conclusion: Most hospitalized patients with MI have limited HL, and their HL has a significant relationship with rehospitalization.